2012
DOI: 10.1016/j.mechrescom.2012.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on biomechanical growth and remodeling mechanisms in glaucoma

Abstract: Glaucoma is a blinding diseases in which damage to the axons results in loss of retinal ganglion cells. Experimental evidence indicates that chronic intraocular pressure elevation initiates axonal insult at the level of the lamina cribrosa. The lamina cribrosa is a porous collagen structure through which the axons pass on their path from the retina to the brain. Recent experimental studies revealed the extensive structural changes of the lamina cribrosa and its surrounding tissues during the development and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
47
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 110 publications
1
47
2
Order By: Relevance
“…Structural changes of the LC and its surrounding tissues during the development and progression of glaucoma have already been described. 22,23 On the other hand, we did not find significant statistical correlation between structural changes and preoperative prelaminar thickness or RNFL thickness.…”
Section: Discussioncontrasting
confidence: 82%
“…Structural changes of the LC and its surrounding tissues during the development and progression of glaucoma have already been described. 22,23 On the other hand, we did not find significant statistical correlation between structural changes and preoperative prelaminar thickness or RNFL thickness.…”
Section: Discussioncontrasting
confidence: 82%
“…While each phenomenon is measured individually, our parameter post-BMO total prelaminar volume 7,9 captures all three. Third, connective tissue remodeling 11,12,15 not only contributes to the stiffening processes whereby reversible deformations become permanent, it separately underlies the phenomena of laminar insertion migration, 9,16,17 laminar thickness change, 11 and retrolaminar septal recruitment. 11 The purpose of this report is to identify the principal components of ONH connective tissue deformation and remodeling in monkey experimental glaucoma.…”
mentioning
confidence: 99%
“…Many clinical and experimental observations suggest that the response of the laminar tissue to changes in IOP is not uniform. For example, loss of collagen fibers was reported in the top-centre of the lamina and recruitment of new collagen was detected at the lower surface, causing cupping in the lamina of animals suffering from prolonged IOP elevation [5]. It would be interesting to further develop the model to investigate whether and to what extent this non-uniform growth and remodeling of the collagen within the lamina is mediated by blood perfusion and availability of nutrients.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have indicated that chronical IOP elevation induces significant structural changes in a thin porous tissue at the base of the optic nerve head called lamina cribrosa [2][3][4][5][6]. Elevated IOP may lead to vision loss by inducing mechanical damage on the retinal ganglion cells axons passing through the lamina (mechanical hypothesis) [7,8] and/or by altering the blood flow within the lamina's tissue (hemodynamical hypothesis) [9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation